Answer:
y -3 = -1/3(x -4)
Explanation:
The 2-point form of the equation of a line is useful for this. For points (x1, y1) and (x2, y2), it tells you the equation can be written as ...
... y -y1 = (y2 -y1)/(x2 -x1)·(x -x1)
For your given points, this is ...
... y -3 = (6 -3)/(-5-4)(x -4)
... y -3 = -1/3(x -4) . . . . . simplifiied a bit
_____
Comment on the solution
The problem asks for "an equation", so no particular form is required. The 2-point form is the most convenient here. In standard form, the equation would be: x +3y = 13.